KEARIFAN LOKAL SEBAGAI SALAH SATU MODEL KOMUNIKASI PARIWISATA DI DESA CARANGWULUNG, KABUPATEN JOMBANG - Rohimah, Afifatur; Hariyoko, Yusuf; Ayodya, Beta Puspitaning (Universitas 17 Agustus 1945 Surabaya, 2018)
Tourism of a particular area that has been wrestled with local wisdom can become a tourism commodity in the field of promotion, that it can be sold as an attraction for a tourist attraction to the community. If a local wisdom is packaged in a form of tourism communication, it can be one of the elements of the formation of a local branding from a particular region. This research seeks to understand more about a local socio-cultural aphorism in the Carangwulung region, Jombang. Researchers wanted to know a complete and clear picture of a social phenomenon. Local wisdom in managing tourism in Carangwulung Village requires a strong commitment between various parties to obtain mutual welfare. Through the tourism management multileps model, effective communication is established in the management of tourism potential in Carangwulung Village. The bottom up system is run as a way to increase tourism based on local wisdom. Tourist attractions are managed by following IPTEK, but still based on the social and cultural conditions of the Carangwulung.Keywords: tourism communication, local wisdom, Carangwulung